On the Collisional Disalignment of Dust Grains in Illuminated and Shaded Regions of IC 63 - Soam Archana; Andersson B-G; Acosta-Pulido Jose; Lopez Manuel F; Vaillancourt John E; Weaver Susanna LW; Piirola Vilppu; Gordon Michael S (IOP PUBLISHING LTD, 2022)
Interstellar dust grain alignment causes polarization from UV to mm wavelengths, allowing the study of the geometry and strength of the magnetic field. Over the last couple of decades, observations and theory have led to the establishment of the radiative alignment torque mechanism as a leading candidate to explain the effect. With a quantitatively well constrained theory, polarization can be used not only to study the interstellar magnetic field, but also the dust and other environmental parameters. Photodissociation regions, with their intense, anisotropic radiation fields, consequent rapid H-2 formation, and high spatial density-contrast provide a rich environment for such studies. Here we discuss an expanded optical, NIR, and mm-wave study of the IC 63 nebula, showing strong H-2 formation-enhanced alignment and the first direct empirical evidence for disalignment due to gas-grain collisions using high-resolution HCO+(J = 1-0) observations. We find that a relative amount of polarization is marginally anticorrelated with column density of HCO+. However, separating the lines of sight of optical polarimetry into those behind, or in front of, a dense clump as seen from gamma Cas, the distribution separates into two well defined sets, with data corresponding to "shaded" gas having a shallower slope. This is expected if the decrease in polarization is caused by collisions since collisional disalignment rate is proportional to R-C proportional to n root T. Ratios of the best-fit slopes for the "illuminated" and "shaded" samples of lines of sight agrees, within the uncertainties, with the square root of the two-temperature H-2 excitation in the nebula seen by Thi et al.